2022
DOI: 10.1039/d2an01059c
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication and characterization of multispecies electroactive biofilms in stratified paper-based scaffolds

Abstract: Bioelectrochemical technologies have attracted significant scientific interest because the effective bacterial electron exchange with external electrodes can provide a sustainable solution that joins environmental remediation and energy recovery. Multispecies electroactive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Very recently, our group partially demonstrated that the paper-based platform can find the best-fit solution to form densely packed aggregates of bacterial cells. 36 We successfully created multispecies co-culture systems and controllable spatiotemporal gradients of oxygen, nutrients, and bacterial waste products. Despite excitement about these achievements, however, studies could not explore whether the cells cultured in paper are a simple bacterial aggregate in the planktonic phase or an actual physiologically defined biofilm that can represent a new in vitro model for biofilm formation and development.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, our group partially demonstrated that the paper-based platform can find the best-fit solution to form densely packed aggregates of bacterial cells. 36 We successfully created multispecies co-culture systems and controllable spatiotemporal gradients of oxygen, nutrients, and bacterial waste products. Despite excitement about these achievements, however, studies could not explore whether the cells cultured in paper are a simple bacterial aggregate in the planktonic phase or an actual physiologically defined biofilm that can represent a new in vitro model for biofilm formation and development.…”
Section: Resultsmentioning
confidence: 99%
“…Then, Shewanella oneidensis , an electrogenic bacteria demonstrating high metabolic rate and power generation, was inoculated into the 3D fibrous structure (Figure 4C). [ 54 ] Wax penetration formed the proton exchange membrane (PEM) so that the metabolically produced protons can be diffused to the cathode while the electrons move externally along the circuit (Figure 4D). Due to the cathode material having a low over‐potential, the cathode was prepared by introducing an Ag 2 O catalyst diluted in the PEDOT: PSS solution (Figure 4E).…”
Section: Resultsmentioning
confidence: 99%
“…Here, Pseudomonas aeruginosa was selected as a model weak electrogenic pathogen. Our previous paper-based platforms for microbial cultivation 26 and paper-based microbial fuel cells 27 for sensing were revolutionarily changed for innovative AST in biofilm. Three hexagonal-shaped tabs prepared on a 2-D paper sheet developed a 3-D functional device by folding the paper twice.…”
Section: Bacteria Device Design and Operationmentioning
confidence: 99%
“…Previously, our group had comprehensively explored the biofilm formation in papers, demonstrating fast accumulation and acclimation of the bacteria. 19,26 Paper as a substrate provides strong mechanical support for rapidly and controllably constructing a 3-D biofilm. Our microbial fuel cell monitored the biofilm growth in the presence of antibiotics, allowing in situ and real-time phenotypic screening with direct clinical and therapeutic relevance.…”
Section: Bacteria Device Design and Operationmentioning
confidence: 99%